Catalytic nitriding of steel components operating in difficult conditions of hydro-abrasive wear - Larisa Petrova; Alexander Malakhov; Peter Demin; Khushnuda Sharifhodgaeva; Nodirjon Tursunov (Zien Journals, 2022)
In the paper, the catalytic effect of previously deposited copper oxide film on nitriding process is described. Mechanisms of iron nitriding intensification are discussed: ammonia dissociation, nitrogen ions adsorption at metal surface, and nitrides formation acceleration. Microstructure of nitrided layers in Armcoiron and in high-chromium steel is examined. It was shown the increase of abrasive wear resistance of nitrided 20Cr13 steel.
Keywords: Nitriding; chromium steel; catalytic effect; nitrided layer